Assistive technologies to address capabilities of people with dementia: from research to practice - Kenigsberg, Paul-Ariel; Aquino, Jean-Pierre; Bérard, Alain; Brémond, François; Charras, Kevin; Dening, Tom; Dröes, Rose-Marie; Gzil, Fabrice; Hicks, Ben; Innes, Anthea; Nguyen, Mai; Nygård, Louise; et al. (SAGE, 2017)
Assistive technologies (AT) became pervasive and virtually present in all our life domains. They can be either an enabler or an obstacle leading to social exclusion. The Fondation Médéric Alzheimer gathered international experts of dementia care, with backgrounds in biomedical, human and social sciences, to analyse how AT can address the capabilities of people with dementia, on the basis of their needs. Discussion covered the unmet needs of people with dementia, the domains of daily life activities where AT can provide help to people with dementia, the enabling and empowering impact of technology to improve their safety and wellbeing, barriers and limits of use, technology assessment, ethical and legal issues. The capability approach (possible freedom) appears particularly relevant in person-centered dementia care and technology development. The focus is not on the solution, rather on what the person can do with it: seeing dementia as disability, with technology as an enabler to promote capabilities of the person, provides a useful framework for both research and practice. This article summarizes how these concepts took momentum in professional practice and public policies in the past fifteen years (2000-2015), discusses current issues in the design, development and economic model of AT for people with dementia, and covers how these technologies are being used and assessed.